THE EFFECT OF TAX INCENTIVES ON FINANCIAL PERFORMANCE OF MICRO, SMALL, AND MEDIUM ENTERPRISES DURING THE COVID-19 PANDEMIC - Sri Ayem; Nur Hijayanti (Jurnal Ilmu Manajemen Profitability, 2022)
This study aims to determine whether tax incentives have an effect on the financial performance of Micro, Small and Medium Enterprises ( MSMEs ) during the COVID-19 pandemic. The data used for hypothesis testing is using primary data obtained through distributing questionnaires to MSME taxpayers in the Yogyakarta region. The analytical method used to answer the truth of the hypothesis is multiple linear regression. After the data is analyzed, the results show that income tax incentives for MSMEs, Value-Added Tax (VAT) incentive have a positive effect on the financial performance of MSMEs during the COVID-19 pandemic. Meanwhile, the article 25 income tax incentive did not affect the financial performance of MSMEs during the COVID-19 pandemic